PENINGKATAN KEMAMPUAN GURU SD MELALUI SUPERVISI KLINIS - Lukman Lukman; Achmad Supriyanto; Burhanuddin Burhanuddin (Graduate School of Universitas Negeri Malang, 2016)
This study aimed to investigate the improvement of the teachers’ ability and find out the barriers and solutions in clinical supervision activities. The study used the descriptive qualitative approach with a single data analysis. The collection of data through observation, interviews, and documentation. The instruments used in the form of interview guidelines and checklist. The results showed (1) The improvement could be seen in the ability of the teachers in lesson planning; (2) Clinical Supervision ran with three stages, an initial meeting, observations and gathering feedback; (3) The obstacle was not maximal in the use of media and classroom management in the learning process and for the solutions, teachers should use media that attract and manage students’ class in the form of small groups. Penelitian ini bertujuan mengetahui peningkatan kemampuan guru dan mengetahui hambatan serta solusi dalam kegiatan supervisi klinis. Penelitian menggunakan pendekatan kutatif deskriptif dengan ansis data tunggal. Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Instrumen yang digunakan berupa pedoman wawancara dan chek-list. Hasilnya menunjukkan (1) peningkatan kemampuan guru terasa dalam perencanaan pembelajaran; (2) supervisi klinis berjalan dengan tiga tahap, pertemuan awal, observasi, dan pertemuan balikan; (3) hambatannya adalah belum maksimalnya penggunaan media dan pengelolaan kelas dalam proses pembelajaran serta solusinya, guru mesti menggunakan media yang menarik dan mengelola kelas siswa dalam bentuk kelompok kecil.